2006
DOI: 10.1258/095646206778691176
|View full text |Cite
|
Sign up to set email alerts
|

HSV-2 antibodies in female sex workers in Vietnam

Abstract: Little information is available on the prevalence of herpes simplex type-2 (HSV-2) antibodies among groups at potential high risk of HIV in Asia. This study was carried out to determine the prevalence of HSV-2 antibodies and correlates of HSV-2 infection in female sex workers (FSWs) in border provinces of Vietnam. Nine hundred and four FSWs in five border provinces of Vietnam were interviewed about selected sociodemographic and behavioural characteristics, and information about partners by a standard interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The HSV-2 prevalence differential parallels the differential in invasive cervical cancer incidence (26.0/100,000/year in HCMC, 6.3/100,000 in Hanoi18,19), for which HSV-2 may be a cofactor with high-risk HPV infection20. Also, HSV-2 seroprevalence in female sex workers is higher in southern provinces (Dong Thap 32.3%, An Giang 33.3% and Kien Giang 29.9%) than in a northern border area (Lai Chau 5.0%)21. Such regional differences could reflect South Vietnam’s greater mid-20 th century wartime exposure to social, economic, and political disruption, internal migration, and U.S. military personnel and contractors.…”
Section: Discussionmentioning
confidence: 99%
“…The HSV-2 prevalence differential parallels the differential in invasive cervical cancer incidence (26.0/100,000/year in HCMC, 6.3/100,000 in Hanoi18,19), for which HSV-2 may be a cofactor with high-risk HPV infection20. Also, HSV-2 seroprevalence in female sex workers is higher in southern provinces (Dong Thap 32.3%, An Giang 33.3% and Kien Giang 29.9%) than in a northern border area (Lai Chau 5.0%)21. Such regional differences could reflect South Vietnam’s greater mid-20 th century wartime exposure to social, economic, and political disruption, internal migration, and U.S. military personnel and contractors.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the first (baseline) survey among 911 FSWs held during December 2002-January 2003 are reported elsewhere. [11][12][13][14] All participants in the baseline survey were offered azithromycin 2 g stat dose to cover possible cervical infections with gonorrhoea and CT. In December 2004, 982 FSWs were sampled from the same provincial districts as the first survey.…”
Section: Sti/hiv Surveysmentioning
confidence: 99%
“…[11][12][13][14] Selected social, demographical and sexual behaviours among FSWs and their partners in 2004 In all, 982 people participated in the final survey, 99% of whom agreed to give blood and 97% agreed to give urine for testing. Very few of those who were asked to participate declined.…”
Section: Baseline Surveymentioning
confidence: 99%
“…3 There are little data on HSV infection rates in Vietnam, but 1 study of female sex workers in 3 Mekong Delta provinces showed HSV-2 antibody prevalence rates of 30% to 33%. 4 Atypical presentations of herpes are not uncommon in immunocompromised patients. 4 Ulcers can appear in single or multiple locations and are more likely to become chronic and extensive.…”
Section: Discussionmentioning
confidence: 99%
“…4 Atypical presentations of herpes are not uncommon in immunocompromised patients. 4 Ulcers can appear in single or multiple locations and are more likely to become chronic and extensive. Herpes simplex virus lesions in the HIVinfected patient can usually be treated with acyclovir, although acyclovir-resistant HSV has been reported.…”
Section: Discussionmentioning
confidence: 99%